The Role of Cloud Computing in Learning from a Logistic and Strategic Vision - Khoulji, Samira; Bourekkadi, S.; Omari, O.; Slimani, K.; Gamal, A; Kerkeb, M.L. (Transactions on Engineering and Computing Sciences, 2017)
This research focuses on the role of cloud computing from a logistic and strategic vision in organizations. Our research question focuses on understanding the difficulties and limitations that bring the support of steering direction function of information systems in the use of cloud computing in an organization. An exploratory study was conducted with an organization. The results are presented in this article in which we start with an introduction concerning cloud computing. This article includes also an understanding of this effective solution. Meanwhile, our work involves also citing changes of the case study after using cloud computing emphasizing on financial and material gains. In brief, this article discusses one of the most important subjects in the field of management, methodology and management. Especially through the presence of ERP within companies which becomes a compulsory element and not one of the choices.